Demand Analysis for Large Animal and Poultry Meat in Indonesia: An ARDL Perspective - Muksalmina, Muksalmina; Nasir, Muhammad; Sartiyah, Sartiyah (Ekonomikalia Journal of Economics, 2024)
This study examines the growing demand for large livestock and poultry meat in Indonesia, reflecting changing consumption patterns and economic growth. However, this phenomenon faces challenges such as price fluctuations between provinces, declining per capita income, and supply-demand gaps that affect access to and consumption of animal protein. Utilizing panel data from 34 provinces covering the period from 2015 to 2022 and employing an Autoregressive Distributed Lag (ARDL) model, this study analyzes the short- and long-run relationships in meat demand. The results indicate that in the short run, meat prices and per capita income significantly influence demand, while tuna prices have no noticeable effect. In the long run, meat prices, per capita income, and fish prices as substitutes affect meat demand. This study contributes to the development of the livestock sector in Indonesia, provides information for farmers to plan production, and advises the government to educate the public about protein sufficiency and conduct market operations to stabilize prices and maintain meat availability. The findings are expected to help fulfill the current and future demand for meat from large livestock and poultry in Indonesia.